2014
DOI: 10.1371/journal.pgen.1004561
|View full text |Cite
|
Sign up to set email alerts
|

A Model-Based Approach for Identifying Signatures of Ancient Balancing Selection in Genetic Data

Abstract: While much effort has focused on detecting positive and negative directional selection in the human genome, relatively little work has been devoted to balancing selection. This lack of attention is likely due to the paucity of sophisticated methods for identifying sites under balancing selection. Here we develop two composite likelihood ratio tests for detecting balancing selection. Using simulations, we show that these methods outperform competing methods under a variety of assumptions and demographic models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
281
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(293 citation statements)
references
References 71 publications
12
281
0
Order By: Relevance
“…One study has highlighted DMBT1 to be a strong candidate for ancient balancing selection in the genome (49). Another recent study has identified the region upstream of DMBT1 to show unusually negative Tajima's D (in the fifth percentile genome wide) in Europeans, supporting our model of selection (50).…”
Section: Discussionsupporting
confidence: 61%
“…One study has highlighted DMBT1 to be a strong candidate for ancient balancing selection in the genome (49). Another recent study has identified the region upstream of DMBT1 to show unusually negative Tajima's D (in the fifth percentile genome wide) in Europeans, supporting our model of selection (50).…”
Section: Discussionsupporting
confidence: 61%
“…This conclusion should not be taken to mean that balancing selection is ubiquitous across the genome. Population genomics results provide little evidence for balancing selection, suggesting only a scattering of loci across the genome with alleles that have been maintained at intermediate frequencies by selection for periods of time that are much larger than the mean neutral coalescence time (77,(89)(90)(91). However, it is well known that such loci contribute disproportionately to the genetic variance, so that a relatively small number could cause most of it, even if the vast majority of individual variants affecting fitness were kept at low frequencies by purifying selection (5).…”
Section: Discussionmentioning
confidence: 99%
“…The high diversity is thought to be driven by balancing selection acting on several individual genes combined with an overall small recombination rate in the MHC (DeGiorgio et al 2014). Genome-wide association studies have revealed the MHC to be the most important region in the human genome for disease associations, in particular for autoimmune diseases (Trowsdale and Knight 2013;Zhou et al 2016).…”
mentioning
confidence: 99%